Processing-structure-property relationship for electrospun polylactic acid (PLA)/halloysite nanotube (HNT) composite mats - Dong, Yu; Marshall, Jordan; Haroosh, Hazim Jasim Mohammed (Nanjing University of Aeronautics and Astronautics, 2014)
Polylactic acid (PLA)/halloysite nanotube (HNT) composite mats were successfully fabricated via electrospinning. Their processing-structure-property relationship was investigated on the basis of several characterisation techniques including scanning electron microscopy (SEM), mechanical testing, X-ray diffraction (XRD) analysis and differential scanning calorimetry (DSC). Composite mats reinforced by both unmodified and modified HNTs with a dispersant BYK-9067 were prepared at the HNT contents of 0, 1, 5 and 10 wt%/v. Tensile moduli and strengths of composite mats were found to significantly increase up to maximum 365% and 121%, respectively as opposed to those of electrospun PLA counterparts when using additional HNTs (particularly for modified HNTs). The SEM observation reveals that HNT inclusions have overall less remarkable impact on average fibre diameters. Additionally, fibre morphology of composite mats appears to be more uniform especially with 5 and 10 wt% modified HNTs. Moderate HNT intercalation was detected in composite mats with the increasing of d-spacing values for (020), (110) peaks, irrespective of HNT contents and modification. The DSC results confirm the effective HNT nucleation to accelerate PLA cold crystallisation process. Typical modified Halpin-Tsai model and modified Halpin-Tsai laminate hybrid model used in conventional composite theory were found difficult to predict the entire experimental data of elastic moduli for PLA/HNT composite mats, which may be ascribed to the nanosized effect of HNTs and some of electrospun PLA fibres.